Allahu Akbar: When the Imaginative, the Beautiful and the Ethical Meet in Muslim Futures - Bolghiran, Sara (Journal of Muslims in Europe, 2024)
This article explores and situates the manifestation of Muslim futures, a socio-ethical and aesthetic movement encompassing young Muslims creating artworks in which they engage a wide range of moral dilemmas ranging from systemic oppression (in both Islamic and non-Islamic countries), unequal wealth distribution, to the consequences of climate change. Taking a Muslim futures exhibition in Berlin as point of entry, this article argues that within the praxis and intellectual paradigms of imagining and articulating Muslim futures, the entities of ethics imagination (khayal), ethics (akhlaq), and beauty (jamal) are intrinsically linked and paramount in an understanding of how the Islamically meaningful influences these endeavors. This paper aims to contribute to understandings of Muslim subjectivity through a decolonial framework by situating analysis into a non-secular framework of reference, exercising the latest calls to go “beyond the human horizon”, placing the spiritual undertones of the project at the center of consideration.